Hybrid power system options for off-grid rural electrification in northwestern region of Nigeria - Boluwaji Moses Olomiyesan; Onyedi David Oyedum (Academia Green Energy)
Electrical power supply is inadequate in Nigeria, and most remote settlements in the country are not connected to the national grid. This study, therefore, investigates a set of possible off-grid hybrid power systems that can meet the electrical load of a model rural community of 100 households in Kaduna and Katsina States in the northwestern region of Nigeria at the lowest energy cost. Two off-grid hybrid power systems and a stand-alone diesel generator are modeled, simulated, and analyzed for the two locations with different solar and wind energy resources using Hybrid Optimization Model for Electric Renewable (HOMER Pro 3.7.5) software. The optimization results show that a PV-wind-diesel hybrid power system is sufficient to meet the load demand of the two locations at the least cost. The net present cost (NPC) and cost of energy (COE) for the optimal system are US$435,818 and 0.203 US$/kWh in Kaduna and US$322,091 and 0.150 US$/kWh in Katsina. Thus, the optimal system in Katsina has lower NPC than that in Kaduna. In comparison to the grid tariff in Nigeria, the reported cost of energy in this study is cost effective for rural settlements that are far from the existing grid. Thus, the hybrid PV-wind-diesel system is recommended for Kaduna and Katsina. The adoption of this hybrid system in the study locations will boost the social, educational, and economic activities in the villages leading to better education, improved healthcare delivery and enhancement of local businesses.